(untitled) (Indian Journal of Animal Production and Management, 2024)
Data of Gir crossbred calves, maintained at Research cum Development Project on Cattle, Mahatma Phule Krishi Vidyapeeth, Rahuri, for a period from 2005 to 2019 was collected to study effect of genetic and non-genetic factors on survivability traits of calf. The traits studied were cumulative survivability within 0 to 15 days, 0 to 30 days, 0 to 90 days, 0 to 180 days and 0 to 365 days. The least square means of cumulative survivability per cent of Gir crossbred calves at 0 to 15, 0 to 30, 0 to 90, 0 to 180 and 0 to 365 days were 83.27±2.16, 75.40±2.57, 62.29±2.99, 53.96±3.16 and 52.16±3.17, respectively. The period of birth had significant (P<0.05) effect on cumulative survivability trait at ages viz., D 0-30, D 0-90, D 0- 180 and D 0-365. Parity of dam and season of birth had non-significant effect on cumulative calf survivability traits. Significant (P<0.05) effect of calves’ sex on survivability traits was recorded at 0- 15, 0-30, 0-90, 0-180 and 0-365 days. Birth weight of calf had significant (P<0.01) effect on cumulative calf survivability at 0-15 and 0-30 days after birth. The paternal half sib method was use to estimate heritability for cumulative survivability traits the values were low in magnitude, ranged from 0.06 to 0.113. The genetic correlation between cumulative survivability traits ranges between 0.38 to 0.95. Survivability patterns of calves with different genetic groups in Gir crossbred calves showed non significant effect.